Sustained efficacy of incobotulinumtoxina repeated injections for upper-limb post-stroke spasticity: A post hoc analysis - Kaňovský, Petr; Elovic, Elie P; Munin, Michael C; Hanschmann, Angelika; Pulte, Irena; Althaus, Michael; Hiersemenzel, Reinhard; Marciniak, Christina (Journal of rehabilitation medicine, 2021)
OBJECTIVE: This post hoc analysis assessed the impact of repeated incobotulinumtoxinA injections on muscle tone, disability, and caregiver burden in adults with upper-limb post-stroke spasticity. DESIGN: Data from the double-blind, placebo-controlled main period and three open-label extension cycles of two Phase 3, randomized, multicentre trials were pooled. METHODS: Subjects received incobotulinumtoxinA 400 Units at 12-week intervals (±3 days) (study 3001, NCT01392300) or ≤ 400 Units at ≥12-week intervals based on clinical need (study 0410, NCT00432666). Ashworth Scale (AS) arm sumscore (sum of elbow, wrist, finger and thumb flexor, and forearm pronator AS scores), Disability Assessment Scale (DAS), and Carer Burden Scale (CBS) scores were assessed. RESULTS: Among 465 subjects, from study baseline to 4 weeks post-injection, mean (standard deviation) AS arm sumscore improved continuously: main period, -3.23 (2.55) (placebo, -1.49 (2.09)); extension cycles 1, 2, and 3, -4.38 (2.85), -4.87 (3.05), and -5.03 (3.02), respectively. DAS principal target domain responder rate increased from 47.4% in the main period (placebo 27.2%) to 66.6% in extension cycle 3. Significant improvements in CBS scores 4 weeks post-injection accompanied improved functional disability in all cycles. CONCLUSION: IncobotulinumtoxinA conferred sustained improvements in muscle tone, disability, and caregiver burden in subjects with upper-limb post-stroke spasticity.
Keywords: Upper Extremity; dvojitá slepá metoda; Muscle Spasticity; Neuromuscular Agents; botulinum neurotoxin; botulotoxiny typu A; Stroke; Double-Blind Method; výsledek terapie; caregiver burden; nervosvalové látky; Middle Aged; mužské pohlaví; cévní mozková příhoda; ženské pohlaví; Botulinum Toxins, Type A; Humans; upper limb; lidé středního věku; rehabilitation; duration of effect; incobotulinumtoxinA; horní končetina; svalová spasticita; Female; spasticity; Treatment Outcome; lidé; Male